Cuidado? sim; olhar de gênero? não: os sentidos do cuidado no Caps em documentos técnicos do Ministério da Saúde - Pedrosa, Claudio Henrique (2006)
The aim of this research was to understand the meanings of care in mental health care centers (CAPS) in technical documents published by the Brazilian Ministry of Health as support for the implementation of the Psychiatric Reform, with special consideration to the presence of gender issues in this discussion. Starting with the premise that meaning is the result of the articulation of discursive practices, a discursive analysis of these documents was carried out. In this manner, it was possible to propose that, in documents with a normative function (such as governmental decrees), the notion of care associated with the CAPS assumes primarily a therapeutic meaning directed to a patient that is seen as someone defined by a problematic health condition or mental disturbance. This set of meanings are associated with the notions of healthcare territory and therapeutic project , the latter being characterized by three modalities of care: intensive, semi-intensive and non-intensive. In this frame, psychosocial care appears marked by the contradiction between the offer of a type of psycho-medical care that is set in motion as a device for individual control and, on the other hand, the possibility of implementing creative forms of care aimed at political empowerment and personal autonomy. It was also possible to observe, in the documents that were analyzed in this research, that discursive practices concerning gender issues are rare and there is a total absence of issues related to ethnic/race relations. This absence perpetuates the present distance between the Brazilian psychiatric reform and gender and race advocacy efforts. The results suggest the need to promote connections between these political arenas in order that the movement for psychiatric reform (Luta Antimanicomial) might incorporate race and gender perspectives and these advocacy movements might address psychiatric issues